Draft Genome Sequence of Geobacillus sp. Strain LEMMJ02, a Thermophile Isolated from Deception Island, an Active Volcano in Antarctica - Schultz, Júnia (Microbiol Resour Announc, 2019)
The thermophilic Geobacillus sp. strain LEMMJ02 was isolated from Fumarole Bay sediment on Deception Island, an active Antarctic volcano. Here, we report the draft genome of LEMMJ02, which consists of 3,160,938 bp with 52.8% GC content and 3,523 protein-coding genes.